Novel essential amino acid-sulfanilamide hybrid as safe anti-ulcerogenic agent with anti-helicobacter pylori activity - Awaad, Amani Shafeek; Alafeefy, Ahmed Mahmoud; Alasmary, Fatmah A.S.; El-Meligy, Reham M.; Zain, Mohamed E.; Alqasoumi, Saleh Ibrahim (King Saud University, 2017)
A novel and safe essential amino acid (Leucine) incorporating sulfanilamide was synthesized, and evaluated for its anti-ulcerogenic activity and in vitro anti-Helicobacter pylori activity. The new molecule showed a dose dependent activity against absolute ethanol-induced ulcer in rats, it produced percent protection of control ulcer by 66.7 at dose 100 mg/kg. In addition it showed a potent anti-Helicobacter pylori activity in vitro against 7 clinically isolated strains. The minimum inhibitory concentration (MIC) ranged from 12.5 to 50 μg/ml. The preliminary safety studies and toxicity profile are optimistic and encouraging.